The efficiency of enabling to study mathematics module for first year students - Dabrišienė, Vilija; Šileikienė, Regina Dalytė (Lietuvos matematikos rinkinys, 2004)
The practice and research shows, that usual student, who is taking studies in KTU can’t study higher mathematics successfully, because he hasn’t necessary knowledge and skills. It is necessary to create studying environments, where the student can prepare for studies, if he wishes. One of these ways is the enabling to study mathematics module, which was introduced in KTU. The efficiency of this module was the object of our research. The results of research are presented in this article.